Analysis of Effect of Change Source to Surface Distance (SSD) and the Field Size to Distribution Dose Using Monte Carlo Method-EGSnrc - Intan Dillia Nurhadi; Ridwan Ramdani; Freddy Haryanto; Yudha Satya Perkasa; Mada Sanjaya (Institut Teknologi Bandung, 2019)
Research was conducted to analyze the effect of changes in the distance radiation source to the surface it is called the medium Source to Surface Distance (SSD) and wide exposure field (Field Size) on the distribution of the dose in linear air Accelerator (LINAC) using Monte Carlo - EGSnrc. Monte Carlo simulation is used for modeling and simulation head linac at BEAMnrc. Virtual model of the linac is made based on the data characteristics of the aircraft Linac Varian Clinac iX then its output obtained information characteristic photon beam using BEAMDP, while modeling and simulation phantom done on DOSXYZnrc with the size of the phantom is (40x40x40) cm3 , with the material in the form of water, using a beam of photons 6 MV, testing variation SSD at 80 cm, 90 cm, 100.1 cm, 110 cm, 120 cm and variation field size is (6x6) cm2, (10x10) cm2, (20x20) cm2 to obtain disribution of dosage form of curves Percentage Depth dose (PDD) and Profile dose. The results showed that the smaller distance radiation source to the surface of the medium (SSD) and the greater the broad field (field size), then increasing the dose distribution is obtained. In the SSD and Field Size variation, the radiation dose will continue to rise significantly from the surface of the medium 0 cm to a depth of maximum dose (Dmax), then the dose began to decline after passing the depth Dmax.